2019
DOI: 10.1111/dom.13816
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment satisfaction in patients with type 2 diabetes treated with once‐weekly semaglutide in the SUSTAIN trials

Abstract: Aim To investigate treatment satisfaction with semaglutide, a once‐weekly glucagon‐like peptide‐1 receptor agonist, versus placebo/active comparators in the SUSTAIN clinical trial programme. Methods In SUSTAIN 2–5 and 7, the Diabetes Treatment Satisfaction Questionnaire was used to evaluate patient‐perceived treatment satisfaction, hyperglycaemia and hypoglycaemia. Post hoc subgroup analyses were conducted to explore the effects of gastrointestinal adverse events (GI AEs), weight loss (≥5%) or achieving glycae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
2
8
0
2
Order By: Relevance
“…In fact, in most SUSTAIN trials, patients on semaglutide reported better overall treatment satisfaction over comparators. 27 Along with increased patient satisfaction, the approval of Wegovy as a weight loss medication could result in more avenues to investigate the many underlying mechanisms of weight loss by GLP-1 RAs. Presently, most animal and human studies exploring these mechanisms have been conducted using liraglutide.…”
Section: Summary Of Sustain Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in most SUSTAIN trials, patients on semaglutide reported better overall treatment satisfaction over comparators. 27 Along with increased patient satisfaction, the approval of Wegovy as a weight loss medication could result in more avenues to investigate the many underlying mechanisms of weight loss by GLP-1 RAs. Presently, most animal and human studies exploring these mechanisms have been conducted using liraglutide.…”
Section: Summary Of Sustain Evidencementioning
confidence: 99%
“…In fact, in most SUSTAIN trials, patients on semaglutide reported better overall treatment satisfaction over comparators. 27 …”
Section: Summary Of Sustain Evidencementioning
confidence: 99%
“…Additionally, CV benefits and positive effects on some kidney outcomes have been shown with OW semaglutide in participants with T2D 22,23 . Compared with BBI, the lower number of injections required with OW semaglutide may also enhance treatment adherence and QoL 8,24,25 …”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported outcomes assess psychological aspects such as treatment satisfaction, patient wellbeing, health status, and quality of life to complement clinical outcomes and provide an understanding of the physical, social, and emotional impact of treatment regimens (36). For the SUSTAIN trials shown, estimated mean changes from baseline in body weight included only data obtained before initiation of any rescue medication or before premature treatment discontinuation.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%